Formulating The Principle of Intermediary Liability Based On John Rawls' Distributive Justice - Maslihati Nur Hidayat; Agus Surono; Tubagus Achmad Darodjat (PT. Global Research Collaboration, 2026)
The rapid expansion of Indonesia’s digital economy has transformed platform-based marketplaces into central infrastructures of economic exchange, yet the existing intermediary liability regime under the Electronic Information and Transactions Law (ITE Law) and Ministerial Regulation No. 5/2020 remains predominantly reactive and procedurally oriented. This study examines whether the current safe harbour framework is adequate to ensure substantive justice in digital governance, particularly in relation to risk distribution between platforms, consumers, and micro-entrepreneurs. The objective of this research is to reformulate intermediary liability principles using John Rawls’ theory of distributive justice, especially the principles of fair equality of opportunity and the difference principle. The study employs normative legal research with statutory, conceptual, and philosophical approaches, using Rawlsian justice as an evaluative framework for Indonesia’s platform governance regime. The findings indicate that the notice-and-takedown system under current regulation creates structural asymmetries by shifting evidentiary burdens and enforcement responsibility to users, while platforms retain conditional immunity. This condition results in distributive imbalance in digital market participation and weak protection for vulnerable actors, particularly consumers and micro-sellers. This study contributes theoretically by extending Rawlsian distributive justice into intermediary liability regulation, arguing that digital platforms should be understood as institutional actors responsible for maintaining background justice in digital markets. Normatively, the study proposes a shift toward a proactive liability model based on five principles: proportional duty of care, transparency of algorithmic governance, no-fault compensation mechanisms, inclusive seller verification, and independent algorithmic audits. These principles provide a normative foundation for reforming Indonesia’s intermediary liability regime under the ITE Law and its implementing regulations toward a more equitable and accountable digital governance framework.